The biomechanics of the bone and of metal, Zantex and PEEK bars in normal and osteoporotic condition, surrounding implants over protocols: an analysis by the Finite Element Method (Research, Society and Development, 2022)
This study aims to assess the biomechanical behavior of the alveolar bone surrounding the implants over protocol with metal, Polyether ether ketone (PEEK) and Zantex bars, in normal and osteoporotic conditions.  For the simulation, geometric models of the mandibular arch were designed containing 5 implants and two variables. The first variable is the bone condition - normal and osteoporotic-, and the second is the material used in the protocol bars – metal, PEEK and Zantex. Simulation was performed using the Finite Elements Method. Results showed that the largest load peaks were concentrated in the medullary bone, both in the normal and osteoporotic conditions. The osteoporotic bone was subjected to more loads than the normal bone in all simulated structures. PEEK and Zantex bars are generally effective load dissipators, showing better performance than Ni-Cr in both types of bone. It is important to assess the bone condition and its relationship with the material used in protocol-type prostheses infrastructure.